Can Cost-Benefit Analysis Guide Education Policy in Developing Countries? - Jimenez, Emmanuel; Patrinos, Harry Anthony (World Bank, Washington, DC, 2012)
Cost-benefit analysis in education is an important tool in the economists' arsenal. However, it is essential that research, especially on the social benefits of education, make further progress to make cost-benefit more analysis. There is a need for more research on the effects of policy interventions on outcomes beyond access to a year in school and what they earn as a result, such as on what children actually learn. Such research should focus on ensuring that the interventions are attributable to outcomes. Nevertheless, it is worthwhile to go through the discipline of noting the benefits and costs, even if social rates of return cannot be calculated robustly.